The Relationship Between Nurse Workload and Missed Nursing Care in The Inpatient Room - Fajar Mulia Dewi; Kuswantoro Rusca Putra; Viera Wardhani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Background: nurses in inpatient rooms often miss the provision of nursing care due to the dimensions of assessment, individual needs, basic needs, and planning. The number of additional tasks in nurses’ activities will increase the nurses’ workload that must be completed. Nurses’ duties beyond their physical capacity trigger missed nursing care. Therefore, this study aims to find the relationship between nurses’ workload and missed nursing care in a hospital. Methods: The research design used was observational analysis with a cross-sectional approach. The sample in this study was 156 inpatient nurses at Wava Husada Hospital in Malang with a purposive sampling approach. The research was carried out for 1 month, from February to March 2021. Workload measurement used the Rafaela system method. The MISSCARE Survey Instrument measured missed nursing care. The analysis of workload relationship data with missed nursing care implemented Spearman’s Rho test on SPSS version 26. Results: In the inpatient room, the nurse workload relationship was found based on the patient’s assessment score of dependency level per nurse with missed nursing care on the dimension of the basic need with an ρ-value of 0.027. At the same time, the workload based on the nurses’ professional assessment had no relationship with the missed nursing care or its four dimensions.Conclusion: The relationship between workload in the inpatient room based on the assessment score of the patient dependency level per nurse with missed nursing care occurred on the dimensions of basic needs.